Demystifying role of local distortion in emission colors tuning of lead-free zero-dimensional metal halide nanocrystals - Samanta, Tuhin; Viswanath, Noolu Srinivasa Manikanta; Kim, Hyeon Woo; Jang, Sung Woo; Han, Joo Hyeong; Cho, Sung Beom; Im, Won Bin (Chemical Engineering Journal, 2024)
Photoluminescence (PL) systems that display emission color tuning have recently garned importance because of their significant role in lighting technologies. However, lead-free metal halides (MHs) for tuning emission wavelengths remain elusive owing to their large bandgaps. Herein, the synthesis of a series of highly luminescent lanthanide (Ln)-based zero-dimensional Cs3LnCl6:Sb3+ (CLnC:Sb3+) nanocrystals (NCs), where Ln = Lu3+, Y3+, Gd3+, or La3+, exhibiting tunable emission colors are demonstrated. Structural and density functional theory calculations revealed a direct relationship between the size and local distortion of the LnCl6 polyhedra and, hence, the emitting center, the SbCl6 octahedra. In particular, when the size of LnCl6 increased, the degree of local distortion increased from Lu to La, which enabled tuning of the emission wavelengths. Furthermore, a white-light-emitting device was constructed using CLaC: Sb3+ NCs, which delivered a high color rendering index of 93. The results of this study will pave the way for achieving tunable emission energies in other low-dimensional MHs for next-generation lighting applications.
Keywords: And color tunability; Color tunability; Color tuning; Emission color; Emission wavelength; Lead-Free; Local distortion; Self-trapped emission; Zero-dimensional; Zero-dimensional metal halide; and color tunability; Local distortion; Self-trapped emission; Zero-dimensional metal halides